Leadership during Digital Transformation in the South African Banking Sector - Mahadeo, Zane Jonathan (University of the Witwatersrand, Johannesburg, 2024)
This paper investigated the pivotal role of leadership in the context of digital transformation within the South African (SA) banking sector. The study delved into the various leadership styles, competencies, and practices adopted by banking leaders to propel digital transformation initiatives. As part of this research, qualitative research methods, were applied which included in-depth interviews with senior leaders in the SA banking sector. Through their perceptions and experiences the research sought to uncover critical leadership practices, including the identification of the most suitable leadership styles, the cultivation of a digital culture, and the implementation of effective change management strategies. Moreover, the paper aims to identify the current challenges faced by leaders in navigating the digital transformation landscape. This research will contribute to the existing body of knowledge on leadership during digital transformation in the SA banking sector. It will also enable organisation to harness the full potential of digital advancements and implement competitive strategies to succeed in the ever-evolving banking industry
A research study submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management,Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Digital Transformation; Leadership; South African Banking Sector; UCTD; SDG-8: Decent work and economic growth